Evaluation Of Patients After Canal Wall-Up Tympanoplasty in Dr. Soetomo General Hospital - Hariadi, Ari Trisna; Rahmawati, Rosydiah (Journal of Neonatal Surgery, 2025)
Background: Chronic Suppurative Otitis Media (CSOM) is a chronic inflammation of the middle ear mucosa and mastoid cavity. It is characterized by tympanic membrane perforation and a history of ear canal discharge (otorrhea). CSOM is classified into two types: safe type CSOM (mucosal or benign type) and dangerous type CSOM (bone or malignant type). Canal wall-up tympanoplasty (CWU) surgery is performed to treat the safe type of CSOM. Objective: To describe the profile of the safe type CSOM patients after CWU tympanoplasty in Dr. Soetomo General Academic Hospital. Method: This study was a retrospective descriptive using medical record data at the otology division, ORL-HNS Outpatient, Dr. Soetomo General Academic Hospital Surabaya. The study population was all the safe type CSOM patients who underwent CWU tympanoplasty surgery from January 2018 - December 2020. Result: The study included 76 patients with safe-type CSOM who underwent CWU tympanoplasty. The majority of patients were male, and the highest proportion was in the age groups of 11-20 years and 21-30 years. Tympanic membrane examination revealed that most patients had subtotal perforations (35.14%), and audiometric examination showed conductive deafness in 68.42% of cases. The most common pathology observed in the tympanic cavity during surgery was granulation (69.74%), and type I tympanoplasty was the most frequently performed procedure (77.63%). The majority of tubal function tests showed patent results (56.58%), and Schuller plain radiographs commonly showed sclerotic findings (78.95%). Post-surgery, the majority of patients had dry ears (80.26%), exhibited good growth of eardrum grafts (76.32%), and experienced an improvement in hearing function (60.53%). Conclusion: In this study, the eradication after surgery obtained dry ear conditions with good growth of eardrum grafts and increased hearing function in patients with safe type CSOM after CWU Tympanoplasty.